Applying Multiple Intelligence-Based Activities (Miba) to Promote Students’ Writing Performance - Dahlia Husain (ETERNAL (English Teaching Journal), 2015)
The present study was conducted based on the assumption that accommodating students’ differences in classroom setting will lead to students’ success particularly in language learning. This research was aimed to investigate the extent of the application of Multiple Intelligence-Based Activities (MIBA) to promote students’ writing performance. There are 2 homogenous groups of the 4th semester of English Department students of Gorontalo State University enrolled in this study. A total of 40 students from control and experimental group were involved. This study applied quasi-experimental design with pretest and posttest that were given to both groups followed by the perceptional questionnaire to find out the students’ perception toward the application of MIBA. The experimentation comprised 8 types of activities as the embodiment of 8 intelligences proposed by Gardner (2011) to be incorporated into students’ writing class. The students’ writing performance was measured through Jacobs et. al.’s analytic writing scale (as cited in Hughes, 2003) including content, organization, vocabulary, language use and mechanics, while the data from the questionnaire was analyzed through Likert scale measurement. The result of the independent sample t-test revealed that experimental group taught using MIBA showed a statistically significant performance compared to the control group taught using conventional way of teaching with t-observed value was greater than t-table value (2.532 > 2.042).  At last, the data from perceptional questionnaire strongly suggest that the students of experimental group had positive perception toward the application of MIBA. Therefore, it can be concluded that MIBA gave a positive effect in promoting students’ writing performance.